PENGARUH KEMAMPUAN BERFIKIR KREATIF TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MARKETING KELAS X SMK MANDIRI PONTIANAK - Utami, Nur Eva; Herkulana, Herkulana; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
ABSTRACTThis study aims to determine the effect of the ability to think creatively on student learning outcomes in marketing subjects in marketing class X SMK Mandiri Pontianak. Variables in this study consisted of independent variables (X), Creative Thinking Abilities and variables (Y), Student Learning Outcomes . The method used in this research is quantitative descriptive method with correlational study form. The population in this study was all marketing class X students. While the samples in this study were all students of class X Marketing in Pontianak Mandiri Vocational Schools obtained through saturated sample techniques. The results showed that the ability to think creatively had no effect on student learning outcomes in marketing subjects in class x marketing with the formula Y = 78,975 + 0.306X. Based on the results of calculations using the SPSS program, t arithmetic of 3.472 while t table with 47 student respondents so the degree of freedom df = nk or 47-2 = 45, then t table is 2,014 of these results compared between t arithmetic with t table that is (3,472> 2014) and with a coefficient of determination (R2) 0.310 or 31% which means there is an influence between the ability to think creatively on student learning outcomes in marketing subjects in class X marketing at SMK Mandiri Pontianak. Keywords: Ability, Creative Thinking, Learning Outcomes